Determination of arsenic and lead in lipsticks by atomic absorption spectroscopy that is expanded in Metropolitan Lima - Llahuilla Q., José A. (2020)
In this research study, the concentration of arsenic and lead was determined in eight different brands of lipsticks that are marketed in Metropolitan Lima. Materials and methods Non-experimental cross-sectional design the analytical method used was atomic absorption spectroscopy with a graphite furnace, the analysis of variance was applied to compare multiple means (ANOVA) considering p <0.05 for significance and the Student t-test . Samples were collected randomly in shopping centers and analyzed at the Chemical Analysis Services Unit (USAQ). results, lead values range from 0 ppm to 71.96 ppm, the average concentration being 6.60 ppm, 12.5% of the samples exceed the maximum permissible limits (LMP) of 10 ppm recommended by the Food and Drug Administration (FDA), Values for arsenic range from 0 ppm to 16.59 ppm, the average concentration is 3.34ppm, and 40.6% of the total samples exceed the maximum permissible limits (MPL) of 3 ppm established by the FDA. Conclusion, the average concentration of lead in lipsticks does not exceed the LMPs. values recommended by the FDA, while the average value of arsenic does exceed it.